AN EVALUATION OF ALTERNATIVE DISPUTE RESOLUTION MECHANISMS IN THE AFRICAN REGION - Baboolal, Rashri; Louis Naude (Obiter, 2024)
Alternative dispute resolution (ADR) in Africa is growing and flourishing but the region is not a global leader in conflict resolution. The African region still has many challenges to overcome. The region has the potential to expand, grow and thrive with foreign direct investment to boost its economies and ensure stability for its infrastructure. The African region is rich in many natural resources, but, unfortunately, interstate conflict causes instability to social, political and economic rights. This article explores the weaknesses and challenges within the African region with a view to activating the potential of the region to become a global leader in alternative dispute resolution. The enforcement and implementation mechanisms of alternative dispute resolution require an evaluation of current systems to ensure that there is an animate thrust of dispute resolution. The African systems have their strengths, but an evaluation of any system always exposes weaknesses. Corruption within the African region is a common theme, since government does not play an active role in deterring corruption, and this causes the public to mistrust all initiatives that stem from government influence. The article discusses the situation in four African countries, showing that corruption, lack of education and a lack of skilled ADR practitioners cause a dysfunctional system that cannot embrace ADR. For an ADR system to function smoothly, numerous ADR practitioners are needed to resolve conflict competently. Furthermore, a selective system of favouring laws that support only the government as opposed to investors causes an imbalance, and discourages investors from investing in Africa. A way needs to be paved, not to negate international practices relating to investor disputes, but rather to work holistically with national laws, to harmonise laws and overcome any conflict of law within the region.